Vaccination with an Attenuated Ferritin Mutant Protects Mice against Virulent Mycobacterium tuberculosis. (3rd August 2015) - Subbian, Selvakumar; Pandey, Ruchi; Soteropoulos, Patricia; Rodriguez, G. Marcela
Abstract : Mycobacterium tuberculosis the causative agent of tuberculosis affects millions of people worldwide. New tools for treatment and prevention of tuberculosis are urgently needed. We previously showed that a ferritin ( bfrB ) mutant of M. tuberculosis has altered iron homeostasis and increased sensitivity to antibiotics and to microbicidal effectors produced by activated macrophages. Most importantly, M. tuberculosis lacking BfrB is strongly attenuated in mice, especially, during the chronic phase of infection. In this study, we examined whether immunization with a bfrB mutant could confer protection against subsequent infection with virulent M. tuberculosis in a mouse model. The results show that the protection elicited by immunization with the bfrB mutant is comparable to BCG vaccination with respect to reduction of bacterial burden. However, significant distinctions in the disease pathology and host genome-wide lung transcriptome suggest improved containment of Mtb infection in animals vaccinated with the bfrB mutant, compared to BCG. We found that downmodulation of inflammatory response and enhanced fibrosis, compared to BCG vaccination, is associated with the protective response elicited by the bfrB mutant.